Academic content collection ([United Kingdom] : Thomson Heinle, 2007)
Collection of 6 stories for reader's practice and reinforcement
t The Navajo -- Dolphins -- Tony Hawk -- Life in a cave -- Energy -- The Statue of Liberty
Title from container
Keywords: Hawk, Tony -- Juvenile literature; Reading; Navajo Indians -- Juvenile literature; Dolphins -- Juvenile literature; Cave animals -- Juvenile literature; Power resources -- Juvenile literature; Statue of Liberty (New York, N.Y.) -- Juvenile literature